Dynamics of Legal Framework for Public-Private Partnership (PPP) in Infrastructure Provision - K, Andriansyah Tiawarman; Fakrulloh, Zudan Arief (Cognitionis Civitatis et Politicae, 2024)
The increasing demand for public infrastructure in Indonesia, coupled with national budget limitations, has elevated the importance of the Public-Private Partnership (PPP) scheme as an alternative financing mechanism. This study aims to analyze the legal framework and challenges associated with the implementation of PPP in infrastructure provision. Using a qualitative approach, the research examines existing regulations, including Presidential Regulation No. 38 of 2015, as well as other supporting policies that form the basis of PPP implementation in Indonesia. The findings reveal two critical aspects: first, the current legal framework for PPP provides a foundation for collaboration but requires enhancement to address gaps in clarity and effectiveness; second, significant challenges, including risk allocation, dispute resolution, and legal protection for parties, hinder the execution of PPP projects. The study concludes that an improved and accountable legal framework is essential to attract private sector investment and ensure the success of PPP projects. Strengthening regulatory certainty and addressing legal challenges are pivotal for fostering sustainable infrastructure development in Indonesia.